Jianpi Yangzheng Xiaozheng decoction alleviates gastric cancer progression via suppressing exosomal PD-L1 - Chen, Yanzhen; Liu, Jiayun; Chen, Yuxuan; Zhang, Ruijuan; Tao, Jialei; Chen, Xu; Wang, Haidan; Sun, Qingmin; Wu, Jian; Liu, Shenlin (Frontiers in Pharmacology, 2023)
Jianpi Yangzheng Xiaozheng decoction (JPYZXZ) is an empirical traditional Chinese medicine formula that has been reported to significantly prolong the survival of patients with advanced gastric cancer (GC). However, its underlying mechanism have not been fully elucidated. The present work aims to explore the possible mechanism of JPYZXZ on regulating GC progression. We firstly confirmed the inhibitory effect of JPYZXZ in GC MKN74 cells and 615-strain mice, which was possibly mediated with IL-6/JAK2/STAT3 pathway dependent PD-L1 expression. Moreover, we showed that JPYZXZ diminished the expression levels of GC-derived exosomal PD-L1 in MFC murine cells and xenograft GC model, as well as stage IIA-IIIB GC patients. We further found that in different types of tumor-infiltrating immune cells, PD-L1 expression was most positively correlated with myeloid-derived suppressor cells (MDSCs) in GC in the TISIDB database. We isolated exosomes derived from supernatants of MFC cells and co-cultured with bone marrow cells derived from C57BL/6 mice, and further revealed that the expansion of MDSCs was mediated by GC-derived exosomal PD-L1. Meanwhile, our results indicated that JPYZXZ inhibited the delivery of exosomal PD-L1 from GC cells to bone marrow cells, thereby alleviating exosomal PD-L1-induced differentiation and expansion of MDSCs in the tumor microenvironment. This led to a decrease in the levels of several immunosuppressive factors, including iNOS, Arg-1, TGF-β, IL-10, and IL-6, in 615-strain mice.Moreover, clinical data also revealed a significant positive relationship between exosomal PD-L1 and polymorphonuclear MDSCs under the JPYZXZ treatment in stage IIA-IIIB GC patients. In conclusion, our study confirmed that exosomal PD-L1 could be a key factor in controlling MDSCs differentiation in GC. JPYZXZ alleviated GC progression via suppressing exosomal PD-L1 mediated expansion of MDSCs, thereby remodeling the immunosuppressive tumor microenvironment, which provided the experimental evidence for the clinical application of JPYZXZ in the treatment of GC via PD-L1.